Additive manufacturing of continuous carbon fiber reinforced poly-ether-ether-ketone with ultrahigh mechanical properties. (August 2020) - Chang, Baoning; Li, Xuemu; Parandoush, Pedram; Ruan, Shilun; Shen, Changyu; Lin, Dong
Abstract: Continuous carbon fiber reinforced poly-ether-ether-ketone (CCF/PEEK) composites have attracted significant interests in mission-critical applications for their exceptional mechanical properties and high thermal resistance. In this study, we additively manufactured CCF/PEEK laminates by the Laser-assisted Laminated Object Manufacturing technique, which was recently reported by the authors. The effects of laser power and consolidation speed on the flexural strength of the CCF/PEEK composites were studied to obtain the optimal process parameters. Hot press postprocessing was performed to further improve the mechanical properties of the composites. Various fiber alignment laminates were prepared, and the flexural and tensile properties were characterized. The hot press postprocessing 3D printed unidirectional CCF/PEEK composites exhibited ultrahigh flexural modulus and strength of 125.7 GPa and 1901.1 MPa, respectively. In addition, the tensile modulus and strength of the composites reached 133.1 GPa and 1513.8 MPa. The results showed that the fabricated CCF/PEEK exhibited superior mechanical performance compare to fused filament fabrication (FFF) printed carbon fiber reinforced thermoplastics (CFRTP). Highlights: Continuous carbon fiber reinforced PEEK composites were additively manufactured by LA-LOM. Effects of process parameters on mechanical properties of the composites were investigated. Hot press postprocessing was performed to further improve the mechanical properties. The tensile and flexural properties of the composite laminates were characterized.